Learning Japanese : textbook for beginners (Just Reality, 2024)
"This book is designed for beginners and those who want to learn the Japanese language step by step. It helps you learn grammar and acquire communication competence in real situations, such as meeting someone for the first time, asking for directions, going shopping, telling time, using transportation, making hotel reservations, counting numbers, discussing family members, eating out, and more. Split into four sections and 20 units, it will give you knowledge of Japan's past, culture, and traditional way of life, as well as the unique idiosyncrasies of the Japanese people and fascinating facts about modern-day Japan." --Amazon.